(3TQM CdajI GHf eGdcs - (3CHhRjO YHO GdQMef Hf Ydj Hf UGdM GdechOj GdaGSj GdeGdcjs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3YHOGdbGOQ Hf EHQGgje Hf Ydj GdahGd s)
(3ChdgG (B:s
(3hHYO, agPG TQM eNJUQ Ydi CdajI GHf eGdc, egPH GdebGUO, hGVM GdeSGdc, jage Hg CdaGXgG s
(3BNQgG (B:s
(3heUdjkG MGd ef GdVejQ aj CMeO hNjQ fHj HOd ef eMeO bO CJjfG Ydi eG CQOfG LeYg ef GdTQM hGdEYQGH aLGA TQMkG eced GdebGUO s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjf hChGFd GdYHGQGJ HNW GdKdK hcJHJ GdhQbI GdChdi Hbde eNJda hHgG fXGe GdJYbjHIs
(3HgG CKQ JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs